2020
DOI: 10.2147/oarrr.s263287
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors Associated with Methotrexate Intolerance in Rheumatoid Arthritis Patients</p>

Abstract: Background Methotrexate (MTX) Intolerance Severity Score (MISS) has been previously validated in the Arabic language and has helped to detect high levels of intolerance in rheumatoid arthritis (RA) patients. The aim of the current study was to evaluate patient and disease characteristics associated with a high risk of MTX intolerance. Materials and Methods A cross-sectional interview-based survey was conducted using adult RA patients as a study group, who were visiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
12
2
Order By: Relevance
“…Therefore, it is widely used as a routine laboratory test for RA diagnosis in clinical practice. [ 19 ] In the present study, anti-CCP was detected in 47 (78.3%) patients, and these findings were inconsistent with investigations conducted by Omair (98.3%)[ 18 ] or Attar (57.2%). [ 16 ]…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is widely used as a routine laboratory test for RA diagnosis in clinical practice. [ 19 ] In the present study, anti-CCP was detected in 47 (78.3%) patients, and these findings were inconsistent with investigations conducted by Omair (98.3%)[ 18 ] or Attar (57.2%). [ 16 ]…”
Section: Discussioncontrasting
confidence: 99%
“…The percentage of patients with a positive RF (66.7%) was comparable to that found in Attar's study (65%). [ 16 ] However, a substantially higher number of patients were observed to have positive RF in research conducted by Omair (93.2%),[ 18 ] Alballa (79.5%),[ 8 ] and Al-Bishri et al . (76.1%),[ 9 ] however; a smaller number was presented in the Attar's study (54%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, csDMARDs side effects, such as mild gastrointestinal symptoms, may negatively impact quality of life and may cause loss of adherence [ 15 ]. Some factors seem to be associated with loss of efficacy, such as female sex or ethnicity, and sex differences on pharmacokinetic have been hypothesized [ 20 ]. Despite csDMARDs being the first line treatment in a previous analysis on 1287 arthritic patients, 34% of patients stopped MTX due to intolerability; therefore, the identification of risk factors associated to intolerability should be further investigated since MTX represents the anchor drug in the treatment of RA [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Arabic MISS (Methotrexate Intolerance Severity Score) was used in this survey and statistical analyses were performed to understand associations between MTX intolerant and MTX tolerant patients. The study found that MTX intolerance was associated with the female gender (adjusted odds ratio (AOR) 6.724; 95% CI 1.420, 31.843, P = 0.016) [48]. Thus, in addition to disease activity, the patient characteristics may significantly affect MTX intolerance.…”
Section: Methotrexate: Mechanism Of Action and Intolerancementioning
confidence: 96%